The phenotype and function of preterm infant monocytes: implications for susceptibility to infection. Issue 3 (19th June 2017) - de Jong, Emma; Strunk, Tobias; Burgner, David; Lavoie, Pascal M; Currie, Andrew
Abstract : Review on preterm infant monocytes and how developmental immaturity of these cells may contribute to preterm infants' susceptibility to infections. Abstract: The extreme vulnerability of preterm infants to invasive microbial infections has been attributed to "immature" innate immune defenses. Monocytes are important innate immune sentinel cells critical in the defense against infection in blood. They achieve this via diverse mechanisms that include pathogen recognition receptor- and inflammasome-mediated detection of microbes, migration into infected tissues, and differentiation into Mϕs and dendritic cells, initiation of the inflammatory cascade by free radicals and cytokine/chemokine production, pathogen clearance by phagocytosis and intracellular killing, and the removal of apoptotic cells. Relatively little is known about these cells in preterm infants, especially about how their phenotype adapts to changes in the microbial environment during the immediate postnatal period. Overall, preterm monocytes exhibit attenuated proinflammatory cytokine responses following stimulation by whole bacterial or specific microbial components in vitro. These attenuated cytokine responses cannot be explained by a lack of intracellular signaling events downstream of pattern recognition receptors. This hyporesponsiveness also contrasts with mature, term-like phagocytosis capabilities detectable even in the most premature infant. Finally, human data on the effects of fetal chorioamnionitis on monocyte biology are incomplete and inconsistent. In this review, we present an integrated view of human studies focused on monocyte functions in preterm infants. We discuss how a developmental immaturity of these cells may contribute to preterm infants' susceptibility to infections.